Drinking Rituals, Masculinity, and Mass Murder in Nazi Germany. Issue 3 (19th September 2018) - Westermann, Edward B.
Abstract: During the Third Reich, alcohol served as both a literal and metaphorical lubricant for acts of violence and atrocity by the men of the Sturmabteilung (SA), the Schutzstaffel (SS), and the police. Scholars have extensively documented its use and abuse on the part of the perpetrators. For the SA, the SS, and the police, the consumption of alcohol was part of a ritual that not only bound the perpetrators together, but also became a facilitator of acts of "performative masculinity"—a type of masculinity expressly linked to physical or sexual violence. In many respects, the relationship among alcohol, masculinity, sex, and violence permeated all aspects of the Nazi killing process in the camps, the ghettos, and the killing fields. After the outbreak of war in September 1939, such practices were increasingly radicalized, with drinking and celebratory rituals becoming key elements for these closed male communities of perpetrators, who used them to prepare for acts of mass killing and, ultimately, genocide. Abstract : Für die Gewalt- und Gräueltaten der Männer von SA, SS und Polizei während des Dritten Reiches diente Alkohol im wörtlichen wie auch im übertragenen Sinn als Schmiermittel. In der Forschung ist der Gebrauch und Missbrauch von Alkohol seitens der Täter ausführlich dokumentiert worden. Alkoholkonsum gehörte für die SA, die SS und die Polizei nicht nur zu einem Ritual, das sie als Täter zusammenschweißte, sondern half ihnen auch zu Taten „performativer Männlichkeit"—eine Männlichkeit, die ausdrücklich mit physischer oder sexueller Gewalt verbunden war. Diese Verbindung zwischen Alkohol, Männlichkeit, Sex und Gewalt durchdrang alle Aspekte der nationalsozialistischen Vernichtungspolitik in den Lagern, Ghettos und auf den „killing fields". Nach dem Kriegsausbruch im September 1939 wurden solche Praktiken zusehends radikalisiert: In diesen geschlossenen männlichen Tätergemeinschaften wurden Trinken und feierliche Rituale zu Schlüsselelementen, um sich auf Massenmord und letzten Endes Genozid vorzubereiten.